2022
DOI: 10.5187/jast.2022.e9
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of chukar partridge (A. chukar) eggs during different conditions (time, turning and position) of storage

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…However, we found that cysteamine supplementation decreased the breaking force in hens at the late stage of egg production. A Haugh unit ≥ 80 indicates a fresh egg, because the Haugh unit decreases as the storage time is extended [29]. In this study, we found that cysteamine supplementation did not influence the Haugh unit in Hy-Line Brown hens at the late stage of egg production, but the Haugh unit decreased in CAU-3 hens at the late stage of egg production.…”
Section: Discussionmentioning
confidence: 53%
“…However, we found that cysteamine supplementation decreased the breaking force in hens at the late stage of egg production. A Haugh unit ≥ 80 indicates a fresh egg, because the Haugh unit decreases as the storage time is extended [29]. In this study, we found that cysteamine supplementation did not influence the Haugh unit in Hy-Line Brown hens at the late stage of egg production, but the Haugh unit decreased in CAU-3 hens at the late stage of egg production.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to albumin and egg yolk, which provide nutrients to the embryos during incubation, the egg shell, which protects its weight values against external environments and is responsible for gas exchange, constitutes the three main elements of an egg (Hincke et al, 2012, Nangsuay et al, 2015. In poultry species, genotype (Tůmová et al, 2009, Lewko et al, 2021Krawczyk et al, 2023;Tadele et al, 2023), rearing conditions ( Tůmová et al, 2011), nutrition (Pérez-Bonilla et al, 2011), age (Akyurek and Okur, 2009;Zita et al, 2013;Chung and Lee, 2014;Park and Sohn, 2018) and storage (Tilki and Saatci, 2004;Demirel and Kırıkçı, 2009;Günhan and Kırıkçı, 2017;Nasri et al, 2020;Çam et al, 2022) affect the external quality of eggs.…”
mentioning
confidence: 99%